2019
DOI: 10.1029/2018jc014882
|View full text |Cite
|
Sign up to set email alerts
|

Summer Carbonate Chemistry in the Dalton Polynya, East Antarctica

Abstract: The carbonate chemistry in the Dalton Polynya in East Antarctica (115°–123°E) was investigated in summer 2014/2015 using high‐frequency underway measurements of CO2 fugacity (fCO2) and discrete water column measurements of total dissolved inorganic carbon (TCO2) and total alkalinity. Air‐sea CO2 fluxes indicate this region was a weak net source of CO2 to the atmosphere (0.7 ± 0.9 mmol C m−2 day−1) during the period of observation, with the largest degree of surface water supersaturation (ΔfCO2 = +45 μatm) in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 88 publications
4
20
0
Order By: Relevance
“…The inferred winter TCO 2 was therefore defined as the average value at 150 m depth in the combined AU1402 and AU1602 data sets (TCO 2 winter = 2,230 μmol kg −1 ; standard deviation = 4 μmol kg −1 ; n = 33). This approach in determining winter TCO 2 follows previous studies in East Antarctic polynyas (e.g., Arroyo et al, 2019;Shadwick et al, 2014) as the temperature minimum on the shelf was not clearly defined and influenced by the presence of Ice Shelf Water (ISW).…”
Section: Seasonal Changes In Tco 2 and Ncp Computationsmentioning
confidence: 96%
“…The inferred winter TCO 2 was therefore defined as the average value at 150 m depth in the combined AU1402 and AU1602 data sets (TCO 2 winter = 2,230 μmol kg −1 ; standard deviation = 4 μmol kg −1 ; n = 33). This approach in determining winter TCO 2 follows previous studies in East Antarctic polynyas (e.g., Arroyo et al, 2019;Shadwick et al, 2014) as the temperature minimum on the shelf was not clearly defined and influenced by the presence of Ice Shelf Water (ISW).…”
Section: Seasonal Changes In Tco 2 and Ncp Computationsmentioning
confidence: 96%
“…The prolonged ice-free conditions also potentially allow enough time for the polynya to take up as much CO 2 as is necessary to reach equilibrium with the atmosphere (Hoppema and Anderson, 2007). However, biological productivity is found to be variable among Antarctic coastal polynyas (Arrigo et al, 2015), and in some cases it is not sufficient to keep a polynya from outgassing CO 2 (Arroyo et al, 2019). Tides can displace water on short timescales (Skogseth et al, 2013;Llanillo et al, 2019) and modify the water column structure through enhanced mixing (Padman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of tides on the marine carbonate chemistry of these biogeochemically impactful regions along the Antarctic coastline remain largely unexplored. Understanding the tidal influence may help us to quantify some of the variability observed among Antarctic polynyas, such as the variability in the biological productivity (Arrigo et al, 2015) as well as the capacity of coastal polynyas to absorb or release atmospheric CO 2 (Arroyo et al, 2019). Practically, this improved understanding can help develop more reliable sampling activities that consider the timing and strength of tidal currents, thereby obtaining representative data of a highly dynamic system.…”
Section: Introductionmentioning
confidence: 99%
“…Surface CO 2 flux is proportional to the downgradient of pCO 2 in the atmosphere and ocean (R. Wanninkhof, 2014). The surface ocean pCO 2 is affected by CO 2 production/consumption due to biological activities, dilution by sea ice/glacial meltwaters, temperature changes, and mixing with ambient water masses (Arroyo et al., 2019; Legge et al., 2017; Shadwick et al., 2017). The decrease of the solubility of CO 2 with increasing water temperature and salinity, in turn, increases pCO 2 in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…In the Southern Ocean, as sea surface temperature increases from winter to summer, primary production increases, and salinity decrease because of the inflow of freshwater from melting sea ice and glacial ice. Several previous studies have pointed out these seasonal effects (Arroyo et al, 2019;Kiuchi et al, 2021;Legge, 2017;Nakaoka et al, 2009;Nomura, 2014;Shadwick et al, 2017). For example, Nakaoka et al (2009) indicated that water column stratification and biology influence oceanic pCO 2 .…”
mentioning
confidence: 98%